Evaluation of mixed mode I/II fracture toughness of C 50/60 from Brazilian disc test - S. Seitl; P. Miarka (Fracture and Structural Integrity)
Durability and sustainability of structures made from concrete like materials is getting more into an interest of civil engineers. Structures are subjected not only to uniaxial load, this means if there is a crack inside the load could be divided into mode I and shear mode II, but also to a mixed mode I/II. Therefore, it is necessary to perform test, which covers mixed mode loads and could be used for specimen made from concrete core-drill. Recommended test specimens used for evaluation of fracture mechanical parameters has usually a prismatic or rectangular shape. The cost of reshaping cylinder into rectangular is expensive and not very efficient, therefore it is very effective to use Brazilian disc test specimen with central notch to obtain mixed mode fracture parameters. The contribution deals with numerical support for Brazilian disc test to obtain calibration curves for mode I and mode II, evaluation of experimental results and compare them with data adapted from literature